The importance of applying translation techniques and tools to enhance translation quality. - Herrera Flores, Kevin Odir; Ruiz Ruiz, Eva Karina; Ventura Lazo, Xiomara Alejandra (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2025)
Disponible en soporte impreso